Update for the practicing pathologist: The International Consultation On Urologic Disease-European association of urology consultation on bladder cancer - Amin, Mahul B.; Smith, Steven C.; Reuter, Victor E.; Epstein, Jonathan I.; Grignon, David J.; Hansel, Donna E.; Lin, Oscar; Mckenney, Jesse K.; Montironi, Rodolfo; Paner, Gladell P.; Al-Ahmadie, Hikmat A.; Algaba, Ferran; et al. (Modern Pathology, 2015)
The International Consultations on Urological Diseases are international consensus meetings, supported by the World Health Organization and the Union Internationale Contre le Cancer, which have occurred since 1981. Each consultation has the goal of convening experts to review data and provide evidence-based recommendations to improve practice. In 2012, the selected subject was bladder cancer, a disease which remains a major public health problem with little improvement in many years. The proceedings of the 2nd International Consultation on Bladder Cancer, which included a 'Pathology of Bladder Cancer Work Group,' have recently been published; herein, we provide a summary of developments and consensus relevant to the practicing pathologist. Although the published proceedings have tackled a comprehensive set of issues regarding the pathology of bladder cancer, this update summarizes the recommendations regarding selected issues for the practicing pathologist. These include guidelines for classification and grading of urothelial neoplasia, with particular emphasis on the approach to inverted lesions, the handling of incipient papillary lesions frequently seen during surveillance of bladder cancer patients, descriptions of newer variants, and terminology for urine cytology reporting.
EVALuna2:6755